Eating Disorder Neuroimaging Initiative (EDNI): a multicentre prospective cohort study protocol for elucidating the neural effects of cognitive–behavioural therapy for eating disorders. Issue 1 (25th January 2021) - Hamatani, Sayo; Hirano, Yoshiyuki; Sugawara, Ayako; Isobe, Masanori; Kodama, Naoki; Yoshihara, Kazufumi; Moriguchi, Yoshiya; Ando, Tetsuya; Endo, Yuka; Takahashi, Jumpei; Nohara, Nobuhiro; Takamura, Tsunehiko; et al.
Abstract : Introduction: Anorexia nervosa is a refractory psychiatric disorder with a mortality rate of 5.9% and standardised mortality ratio of 5.35, which is much higher than other psychiatric disorders. The standardised mortality ratio of bulimia nervosa is 1.49; however, it is characterised by suicidality resulting in a shorter time to death. While there is no current validated drug treatment for eating disorders in Japan, cognitive–behavioural therapy (CBT) is a well-established and commonly used treatment. CBT is also recommended in the Japanese Guidelines for the Treatment of Eating Disorders (2012) and has been covered by insurance since 2018. However, the neural mechanisms responsible for the effect of CBT have not been elucidated, and the use of biomarkers such as neuroimaging data would be beneficial. Methods and analysis: The Eating Disorder Neuroimaging Initiative is a multisite prospective cohort study. We will longitudinally collect data from 72 patients with eating disorders (anorexia nervosa and bulimia nervosa) and 70 controls. Data will be collected at baseline, after 21–41 sessions of CBT and 12 months later. We will assess longitudinal changes in neural circuit function, clinical data, gene expression and psychological measures by therapeutic intervention and analyse the relationship among them using machine learning methods. Ethics and dissemination: The study was approved by The Ethical Committee of the National Center of Neurology and Psychiatry (A2019-072). We will obtain written informed consent from all patients who participate in the study after they had been fully informed about the study protocol. All imaging, demographic and clinical data are shared between the participating sites and will be made publicly available in 2024. Trial registration number: UMIN000039841